Food Habits in the Indian Subcontinent: Making of Cultural Identities - Baral, Raj Kumar; Lamsal, Swarnim Raj (SCHOLARS: Journal of Arts & Humanities, 2021)
This article analyses some popular eating habits in the Indian subcontinent, considering its diversity in its history, especially during the time of colonialism and its religion. Based upon the religious scriptures and postcolonial theorists like Shaobo Xie and Homi K. Bhabha, the article argues that food has its implications beyond the kitchen where it is cooked. Consciously or unconsciously, history and religion have dictated our food choices. Taken together, the references provide new insights into some of the common food items of the Indian subcontinent, showing them as distinct identity markers. Such analysis can help relate our food habits to a broad context and open new avenues to understand the cultural identity of humans through their dietary choices.